2009
DOI: 10.1097/wnr.0b013e32832be7dc
|View full text |Cite
|
Sign up to set email alerts
|

Emotional influences on time perception: evidence from event-related potentials

Abstract: This study examined the influence of emotion on time perception and its neural correlates by measuring event-related potentials. Participants were asked to discriminate a previously memorized 700 ms 'standard' duration from 490, 700 and 910 ms, which were presented by emotional and neutral faces. The results showed decreased contingent negative variation potentials, which index timing, for emotional conditions versus the neutral condition. In addition, under the emotional conditions, the P160 and P240 amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 22 publications
6
31
0
Order By: Relevance
“…Given that emotional information draws attentional resources away from inhibition processing, the subjects had to inhibit emotional processing in order to accomplish the task, thereby leading to an inverted N2. These findings are consistent with Yu et al’s [23] study and a previous study in our laboratory [24] in which N2 was found to be smaller for emotional conditions than for neutral condition. Thus, in the present experiment, the smaller N2 in the NP condition may be a reflection of individuals controling and shifting their attention away from the position where threatening pictures had been presented previously.…”
Section: Discussionsupporting
confidence: 93%
“…Given that emotional information draws attentional resources away from inhibition processing, the subjects had to inhibit emotional processing in order to accomplish the task, thereby leading to an inverted N2. These findings are consistent with Yu et al’s [23] study and a previous study in our laboratory [24] in which N2 was found to be smaller for emotional conditions than for neutral condition. Thus, in the present experiment, the smaller N2 in the NP condition may be a reflection of individuals controling and shifting their attention away from the position where threatening pictures had been presented previously.…”
Section: Discussionsupporting
confidence: 93%
“…Few studies have directly investigated how emotional stimuli interact with neural timing systems to modulate temporal distortions (e.g., 56, 77, 89, 167, 181, 233, 240). A neurobiologically inspired model of time perception, namely the SBF model (4, 158, 159), in conjunction with known mechanisms by which affective stimuli modulate neural activity, may provide an important starting point for assessing how emotional stimuli modulate the inputs and/or outputs of neural timing systems.…”
Section: Putative Neural Mechanismsmentioning
confidence: 99%
“…To date, however, there are very few studies investigating the ERP patterns of the effect of emotion on time perception, except one very preliminary study of our group (Gan et al, 2009). …”
Section: Introductionmentioning
confidence: 96%